Green Museum: Environmental Conservation Strategies Through Innovative Museum Education Programs - Novita Charolis (Biokultur, 2026)
Museums are not only places for preserving cultural heritage but also educational spaces that play an important role in building public environmental awareness. This study examines how museums can contribute to environmental conservation through sustainability-based educational programs. The background of this study is the increasing issue of climate change and the urgent need to strengthen environmental literacy across various segments of society. The methods used include a literature review and observations of environmental education programs in several museums in Indonesia and abroad. The results indicate that museums implementing the concept of a “green museum” through environmentally friendly practices—such as renewable energy management, reduction of plastic waste, and the use of recycled materials in exhibitions—can enhance visitors’ active participation in conservation actions. In addition, interactive educational programs such as recycling workshops, thematic exhibitions on biodiversity, and collaborations with environmental communities are able to create meaningful and sustainable learning experiences. The challenges faced by museums in implementing environmental conservation programs include limited resources, insufficient funding, and a lack of integration between collection management and sustainability initiatives. However, through synergy with educational institutions, government agencies, and local communities, museums can become centers of ecological learning that not only preserve artifacts of the past but also ensure environmental sustainability for future generations. This study concludes that the implementation of environmental conservation strategies in museums is not merely a trend but an urgent necessity. Museums can transform into agents of change that inspire society to maintain harmony between humans and nature.